A clash of Umwelts: Anthropomorphism in behavioral neuroscience - Gomez-Marin, Alex (The Behavioral and brain sciences, 2019)
Brains enjoy a bodily life. Therefore animals are subjects with a point of view. Yet, coding betrays an anthropomorphic bias: we can, therefore they must. Here I propose a reformulation of Brette's question that emphasizes organismic perception, cautioning for misinterpretations based on external ideal-observer accounts. Theoretical ethology allows computational neuroscience to understand brains from the perspective of their owners.